The influence of product market dynamics on a firm's cash holdings and hedging behavior☆ - HAUSHALTER, D; KLASA, S; MAXWELL, W (Journal of Financial Economics, 2007)
Prior work suggests that if a firm shares a larger proportion of its growth opportunities with rivals, an inability to fully invest in these opportunities leads to predatory behavior on the part of rivals and losses in market share. We examine whether firms manage this predation risk. We find inter- and intra-industry evidence that the extent of the interdependence of a firm's investment opportunities with rivals is positively associated with its use of derivatives and the size of its cash holdings. Moreover, an analysis of investment behavior provides evidence that if this interdependence is high, the management of predation risk provides strategic benefits. Our results indicate that predation risk is an important determinant of corporate financial policy choices and investment behavior.